Conflict behavior in the rural community of Siberia: agricultural entrepreneurs and «Kyrgyz population» in context of socio-cultural transformations of late XIX–early XX centuries - I. I. Krott (Омский научный вестник: Серия "Общество. История. Современность")
In the scientific article based on representative sources, issues of conflict behavior between the main «newcomers» social groups and the autochthonous population of the Siberian local community in the late XIX–early XX centuries are considered. The author reveals the external and internal mechanisms for the formation of behavioral strategies, contacts/conflicts of the «Kyrgyz population» and rural entrepreneurs in the region. The publication concludes that entrepreneurs in the agrarian sector and representatives of the «local» community acted as carriers of conflict consciousness, the specificity of which was the warring parties to recognize the opposite of their values, interests, goals and turn them into a motivation for activity. Socio-political and economic changes of the early twentieth century were further gotten confused and complicated the process of relations between the «Kyrgyz» population and agricultural entrepreneurs